623.CONCEPT FOR STUDENT GLASS PAVILION - Bojana, Trajanoska; Elisaveta, Donceva; Daniela, Pana; Hristijan, Gjorgievski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
Contemporary architecture and engineering are based on combining structural glass and steel, where glass is used for its transparency and steel for its strength. The intention behind this pavilion concept is decreasing the lack of modern glass structures in our surrounding. This article describes the FE modelling and analysis of а glass structure planned tо be located in the technical campus of the Faculty of Mechanical Engineering in Skopje. The final exterior of the structure is consisted of five glass frames adhesively bonded and mechanically connected with bolts which give the support of the structure and hold the façade and roof panels. Different scenarios were presented regarding the stability and safety of the glass structure. The carried out FEM simulations are presented, based on predicted static loads, according to the pavilion's location and the climatic parameters. At the end of this article, visual representation of the CAD model within the campus space is given.